1980
DOI: 10.1016/s0006-3495(80)84915-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic forces in muscle and cylindrical gel systems

Abstract: Repulsive pressure has been measured as a function of lattice spacing in gels of tobacco mosaic virus (TMV) and in the filament lattice of vertebrate striated muscle. External pressures up to ten atm have been applied to these lattices by an osmotic stress method. Numerical solutions to the Poisson-Boltzmann equation in hexagonal lattices have been obtained and compared to the TMV and muscle data. The theoretical curves using values for k calculated from the ionic strength give a good fit to experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 17 publications
10
59
0
Order By: Relevance
“…Fibre width declines slightly between pH 7.5 and 6.0, and more steeply below 6.0. This decrease is consistent with other observations of fibre diameter (Maughan & Godt, 1980) and lattice spacing (Rome, 1968;Matsubara & Elliott, 1972), and implies that myofilament charge is involved in determining myofilament lattice spacing (Millman & Nickel, 1980).…”
Section: Forcesupporting
confidence: 92%
“…Fibre width declines slightly between pH 7.5 and 6.0, and more steeply below 6.0. This decrease is consistent with other observations of fibre diameter (Maughan & Godt, 1980) and lattice spacing (Rome, 1968;Matsubara & Elliott, 1972), and implies that myofilament charge is involved in determining myofilament lattice spacing (Millman & Nickel, 1980).…”
Section: Forcesupporting
confidence: 92%
“…X-ray diffraction shows that the condensed DNA is packed into a lattice with well-defined interaxial spacings that decrease with increasing concentration of added polymer (19). The phenomenon is analogous to the immersion of phospholipid bilayers in dextran solutions used by LeNeveu et al (1,2) to measure interbilayer forces and by Millman and Nickel (20) to measure forces between muscle filaments or tobacco mosaic virus particles. Here, as in those systems, under conditions in which PEG is excluded from the DNA lattice, the osmotic pressure of the polymer solution is the osmotic stress compressing the lattice.…”
Section: Methodsmentioning
confidence: 84%
“…Osmotic pressures of PEG 6 and PVP 40 solutions were determined by equilibrium dialysis against PEG 20 A. Zimmerman and Pheiffer (23) and Maniatis et al (19) showed that such DNA samples remain in the B conformation throughout. The diameter of a DNA double helix in this conformation is =20 A.…”
mentioning
confidence: 99%
“…Theories that relate macro molecular interactions to the underlying composition have been formulated [1,2] and tested for different macromolecular as semblies including muscle [3], virus [4], lipid bilayer [5] and biological membranes [6,7], In applying this theory to the myelin sheath, we found that the protein composition and disposition are significant determinants of the electrostatic effects between membrane surfaces and the equilibrium separation be tween them [8,9]. While there is general con sensus that myelin basic protein (MBP) is localized to the cytoplasmic side of the mem branes in central nervous system (CNS) and peripheral nervous system myelins, the orientation of the major integral membrane protein of CNS myelin, proteolipid protein (PLP), has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%